The rise of blockadia as a global anti-extractivism movement. Issue 12 (2nd December 2021) - Chen, Sibo
ABSTRACT: This viewpoint paper discusses the rise of blockadia as a global anti-extractivism movement over recent decades. It elucidates blockadia's distinct characters and implications for future grassroots environmentalism. Collective actions constituting the blockadia movement differ from conventional environmental campaigns in terms of its (1) embrace of confrontational tactics, (2) integration of environmental and social justice concerns, and (3) reliance of grassroots coalitions whose members often have diversified backgrounds. By elaborating these characters, I argue that the rise of blockadia reveals diminishing public trust in capitalism's capacity to avert the worst consequences of climate change. Blockadia thus presents a helpful concept to understand why climate justice activism increasingly bypasses traditional public deliberation mechanisms to intervene in energy policymaking at both state and regional levels.